Diabetes cardiomyopathy: targeted regulation of mitochondrial dysfunction and therapeutic potential of plant secondary metabolites - Pan, Xianglong; Hao, Erwei; Zhang, Fan; Wei, Wei; Du, Zhengcai; Yan, Guangli; Wang, Xijun; Deng, Jiagang; Hou, Xiaotao (Frontiers in Pharmacology, 2024)
Diabetic cardiomyopathy (DCM) is a specific heart condition in diabetic patients, which is a major cause of heart failure and significantly affects quality of life. DCM is manifested as abnormal cardiac structure and function in the absence of ischaemic or hypertensive heart disease in individuals with diabetes. Although the development of DCM involves multiple pathological mechanisms, mitochondrial dysfunction is considered to play a crucial role. The regulatory mechanisms of mitochondrial dysfunction mainly include mitochondrial dynamics, oxidative stress, calcium handling, uncoupling, biogenesis, mitophagy, and insulin signaling. Targeting mitochondrial function in the treatment of DCM has attracted increasing attention. Studies have shown that plant secondary metabolites contribute to improving mitochondrial function and alleviating the development of DCM. This review outlines the role of mitochondrial dysfunction in the pathogenesis of DCM and discusses the regulatory mechanism for mitochondrial dysfunction. In addition, it also summarizes treatment strategies based on plant secondary metabolites. These strategies targeting the treatment of mitochondrial dysfunction may help prevent and treat DCM.